2016
DOI: 10.5430/cns.v4n2p21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude, and practice of nursing management of birth asphyxia in federal medical centre Asaba, Delta State-Nigeria

Abstract: This study aimed at assessing the knowledge, attitude and practice of nursing management of birth asphyxia in Federal Medical Centre Asaba, Delta State, Nigeria. It was a descriptive survey study of 50 nurses selected by purposive sampling technique from the Maternity and Neonatal Units of the centre. Self-structured questionnaire was used to collect data from the nurses on the key aspects of the management of birth asphyxia. The instrument was used in a pilot study in Female medical ward and test retest corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Interestingly, according to the findings of the study by Enweronu-Laryea, Adedemy, Okonkwo, Lee & Robertson, [15] hospitals that provided comprehensive obstetric and newborn care were more likely to have a paediatric team responsible for the newborn around the time of birth and management than hospitals that did not offer such care. This study's findings did not agree with those of Ezenduka, Ndie, & Oburoh, [1] who found that increasing the number of paediatric nurses involved in the management of birth asphyxia resulted in better outcomes for the babies. When it came to the category of staff, the majority of respondents (97.5 percent, or 80 people) were registered nurses/midwives, with 2.5 percent being paediatric nurses as well.…”
Section: Association Of Socio-demographic Factors With Awareness and ...contrasting
confidence: 99%
See 3 more Smart Citations
“…Interestingly, according to the findings of the study by Enweronu-Laryea, Adedemy, Okonkwo, Lee & Robertson, [15] hospitals that provided comprehensive obstetric and newborn care were more likely to have a paediatric team responsible for the newborn around the time of birth and management than hospitals that did not offer such care. This study's findings did not agree with those of Ezenduka, Ndie, & Oburoh, [1] who found that increasing the number of paediatric nurses involved in the management of birth asphyxia resulted in better outcomes for the babies. When it came to the category of staff, the majority of respondents (97.5 percent, or 80 people) were registered nurses/midwives, with 2.5 percent being paediatric nurses as well.…”
Section: Association Of Socio-demographic Factors With Awareness and ...contrasting
confidence: 99%
“…The delivery of a vigorous new-born is widely seen as a splendid manifestation of nature's inherent beauty. The birthing process, despite its relatively short duration, poses the most risk to an individual's life due to its association with the highest mortality rates compared to other stages of life [1]. Upon birth, the neonate undergoes the process of transitioning from intrauterine existence to extra uterine existence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of 17 (34%) are between the ages of 6 and 10. Additionally, 21 (42%) of the sample had no training, whereas 19 (38%) received training[4].The statistical knowledge results result for pediatric nurses' knowledge on Pretest with Posttest regarding neonatal birth asphyxia, that knowledge of nurses concerning neonatal birth asphyxia in general Pretest 50.0% (16) of them at a failure level, Posttest 56.3% (18) of the sample at an excellent level. Knowledge of nurses concerning signs and symptoms of birth asphyxia in the Pretest is 46.9% (15) at the failure level of them; Posttest is 65.6% (21) at an excellent level of them.…”
mentioning
confidence: 98%